The design of the flat slab system with drop panel in the Sukawati market building - Dewa Ngakan Made Dwiva Cahyana; I Nengah Sinarta; I Putu Ellsa Sarassantika (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
Sukawati Market Building has 4 floors and 1 basement with a total building area of 1136.16 m2. It was designed to use a flat slab structure system with the addition of drop panels that maintained the height or story clearance while reducing total building height by eliminating the interior beams. The structure was designed follow the Indonesian Standard for reinforced concrete building design guideline and assessed through finite element simulation. The shear capacity of the flat slab was determined by the strength of the concrete and its dimensions. The reinforcing bar of flat slabs with drop panels is determined in the same way as the reinforcing bar of concrete slabs. Based on the results, the design efficiently resists the forces demand while meeting the deflection requirement, reflecting the structure system's safety and serviceability. The structure system also maintains the total height of the building in order to comply with local high-limit regulation.